2020
DOI: 10.3390/pathogens9090722
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Assessment of Onchocerca Species Transmission by Black Flies in Selected Communities in the West Region of Cameroon

Abstract: The enormity of the public health burden of onchocerciasis motivated the creation of various large-scale control programs that have depended principally on mass treatment of endemic communities with ivermectin for the elimination of the disease. Parasitological evaluation of Onchocerca species in the West Region of Cameroon indicates significant progress in the interruption of parasite transmission in some communities under ivermectin treatment. However, to verify the complete elimination of onchocerciasis, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Human onchocerciasis is one of the most prevalent infectious diseases occurring in developing countries [4]. It is a vector-borne parasitic neglected tropical disease caused by infection with the filarial worm Onchocerca volvulus (O. volvulus) [5]. The disease is transmitted by black flies (Simulium) that acquire microfilariae (larval stage 1) during a blood meal from infected humans.…”
Section: Introductionmentioning
confidence: 99%
“…Human onchocerciasis is one of the most prevalent infectious diseases occurring in developing countries [4]. It is a vector-borne parasitic neglected tropical disease caused by infection with the filarial worm Onchocerca volvulus (O. volvulus) [5]. The disease is transmitted by black flies (Simulium) that acquire microfilariae (larval stage 1) during a blood meal from infected humans.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of the geographic distribution of onchocerciasis in Cameroon revealed that onchocerciasis is endemic in all the ten regions of Cameroon with approximately 60% of the population living in high-risk areas for the disease [ 31 ]. Furthermore, assessment of communities which have been receiving preventive chemotherapy for close to 20 years revealed the continuous spread of the parasite in some communities [ 51 , 52 ]. The OvMCBL02 test is an antibody-based test which is unable to differentiate between past and current infection; thus, control samples were obtained from Rwanda and Europe rather than Cameroon to exclude the possibility of including healthy individuals that may have been infected with the parasite in the past.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Loiasis is concentrated in the rainforest areas of West and Central Africa, with its transmission being reliant on Chrysops flies 14 . In contrast, O. volvulus is transmitted by black flies, Simulium sp 15 …”
Section: Introductionmentioning
confidence: 99%
“…14 In contrast, O. volvulus is transmitted by black flies, Simulium sp. 15 According to the data published by the World Health Organization (WHO) in 1995, onchocerciasis was predominantly found in African countries, as well as certain American and Asian countries. 16,17 It affected over 17.7 million individuals, out of which 270,000 were blind and 500,000 had severe visual impairment.…”
mentioning
confidence: 99%